2018
DOI: 10.1021/jacs.8b03946
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Pd(II) Barrels as Containers for Transient Merocyanine Form and Reverse Thermochromism of Spiropyran

Abstract: Self-assembly of a cis-blocked Pd(II) 90° ditopic acceptor [ cis-(tmeda)Pd(NO)] (M) with a tetradentate donor L [benzene-1,4-di(4-terpyridine)] in 2:1 molar ratio yielded two isometric molecular barrels MB1 and MB3 in DMSO [tmeda = N, N, N' N'-tetramethylethane-1,2-diamine]. Exclusive formation of the symmetrical tetrafacial barrel (MB1) was achieved when the self-assembly was performed in aqueous medium. The presence of a large confined cavity makes MB1 a potential molecular container. Spiropyran (SP) compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 117 publications
5
123
0
Order By: Relevance
“…In the presence of the micelles, signals from both the spiropyran and the merocyanine can be observed in the 1 H‐NMR spectrum (Figure S5). During the photoconversion, the signal from the methyl group on the nitrogen is observed to move from 2.8 to 0.9 ppm . Integration of these signals shows that 55 % of the spiropyran is stabilized as merocyanine in the micelles (as seen in the sample with 1 : 2 molar ratio of zwitterionic repeat unit to spiropyran (Figure S5)), which correlates well with the UV‐Vis spectra showing that, 10 min after turning off the illumination, 58 % of the merocyanine still remains in the micelles.…”
Section: Figuresupporting
confidence: 70%
See 1 more Smart Citation
“…In the presence of the micelles, signals from both the spiropyran and the merocyanine can be observed in the 1 H‐NMR spectrum (Figure S5). During the photoconversion, the signal from the methyl group on the nitrogen is observed to move from 2.8 to 0.9 ppm . Integration of these signals shows that 55 % of the spiropyran is stabilized as merocyanine in the micelles (as seen in the sample with 1 : 2 molar ratio of zwitterionic repeat unit to spiropyran (Figure S5)), which correlates well with the UV‐Vis spectra showing that, 10 min after turning off the illumination, 58 % of the merocyanine still remains in the micelles.…”
Section: Figuresupporting
confidence: 70%
“…During the photoconversion, the signal from the methyl group on the nitrogen is observed to move from 2.8 to 0.9 ppm. [61] Integration of these signals shows that 55 % of the spiropyran is stabilized as merocyanine in the micelles (as seen in the sample with 1 : 2 molar ratio of zwitterionic repeat unit to spiropyran ( Figure S5)), which correlates well with the UV-Vis spectra showing that, 10 min after turning off the illumination, 58 % of the merocyanine still remains in the micelles. We note that each zwitterionic repeat unit probably interacts with multiple merocyanine units, potentially using ionic, dipolar, and π-π supramolecular interactions, since merocyanine-merocyanine aggregates are not observed in the micellar cores.…”
Section: Photobreathing Zwitterionic Micellessupporting
confidence: 67%
“…Confining photochromic molecules in nanometric cavities may profoundly impact their photochemical properties . As previously observed, 1 o can be converted into 1 c by light irradiation at 365 nm ( φ =0.04) and reverted with wavelengths >500 nm ( φ =0.0003, λ irr =550 nm) (see the Supporting Information, Figure S9) .…”
Section: Methodsmentioning
confidence: 64%
“…Confining photochromic molecules in nanometric cavities may profoundly impact their photochemical properties. [46][47][48][49] As previously observed, 1o can be converted into 1c by light irradiationa t3 65 nm (f= 0.04) and reverted withw avelengths > 500 nm (f= 0.0003, l irr = 550 nm) (see the Supporting Information, Figure S9). [50] 1 HNMR experimentss how that both species are quantitatively interconverted (see the Supporting Information,F igure S10).…”
mentioning
confidence: 99%
“…It has been conclusively shown that polystyrene matrix as a supporter for the photochromic compounds contribute to improving photochromic efficiency, sensitivity, isomeric merocyanine stability, and photochromic fatigue resistance, meanwhile, avoiding photochromic compounds aggregation . When it comes to the micron or nanometer level, the polymeric matrix containing the photochromic compounds could be assembled well on a suitable carrier in various manners . Based on the information we have, especially, the electrospun nanofibers could be credibly employed as core components of high performance sensing devices containing the photo‐responsive compounds .…”
Section: Introductionmentioning
confidence: 89%